The learning process from real situations through organic agriculture for the creation of local conservative value and volunteer spirit of youth - Thongphubate, Thanong; Ninlabun, Nualyai; Sisanga, Manit; Chotientip, Tassanee; Maneephruek, Wirat; Tepsud, Punnee (Journal for Developing the Social and Community, 2023)
The purposes of this research were 1) to analyze the learning process to create local conservative value and volunteer spirit of youth with the concept of learning from real situations through organic farming activities and 2) to compare the local conservative value and volunteer spirit of youth who have different experienced organic farming training from learning centers. The research sample consisted of 365 peoples, selected by simple random sampling, secondary school students from 2 schools with learning centers and there were additional courses in the group on organic agriculture in Kamphaeng Saen district, Sampran district, Mueang district and Bang Len district in Nakhon Pathom Province. Data were analyzed by statistics, frequency, percentage, mean, standard deviation, 3-Way MANOVA, independent t-test, ANCOVA and EFA. The results of the research found that (1) the learning process from real situations through organic agriculture for the creation of local conservative value and volunteer spirit of youth consisted of 6 components that could explain the variability of all variables was 92.556% and (2) youth who have different experienced organic farming training from learning centers. There were significantly different scores on local conservative value, with and without experience training on organic farming training from learning centers got an average score of 4.200 and 3.607 respectively, making it believed that Learning by the learning process from real situations through classroom courses or training programs in the learning centers on organic agriculture and social support both inside and outside the family will help create local conservative value of youth.